2015
DOI: 10.1016/j.jvs.2015.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variables in the Vascular Quality Initiative are not reliable predictors of adverse cardiac outcomes or mortality after major elective vascular surgery

Abstract: Objective Heart rate (HR) parameters are known indicators of cardiovascular complications after cardiac surgery, but there is little evidence of their role in predicting outcome after major vascular surgery. The purpose of this study was to determine whether arrival HR (AHR) and highest intraoperative HR are associated with mortality or major adverse cardiac events (MACEs) after elective vascular surgery in the Vascular Quality Initiative (VQI). Methods Patients undergoing elective lower extremity bypass (LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…van Lier et al 1 described tachycardia, anemia, hypoxemia, and hypotension as contributors to myocardial injury because of a supply and demand mismatch. We found mechanical ventilation and heart rate at admission to ICU as independent risk factors for MACE after VS. Scali et al 18 reported less mortality when heart rate was less than 75 beats per minute, but the effect disappeared after controlling for β-blocker therapy. Unfortunately, it was impossible to determine β-blocker therapy in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…van Lier et al 1 described tachycardia, anemia, hypoxemia, and hypotension as contributors to myocardial injury because of a supply and demand mismatch. We found mechanical ventilation and heart rate at admission to ICU as independent risk factors for MACE after VS. Scali et al 18 reported less mortality when heart rate was less than 75 beats per minute, but the effect disappeared after controlling for β-blocker therapy. Unfortunately, it was impossible to determine β-blocker therapy in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes clinical variables collected in operative registries have no clinical value and can lead to incomplete datasets. 60 This analysis has also identified important demographic and clinical factors that influence late survival and such factors should be considered in predictive late survival modelling tools and clinical decision making. 35,54 Varying definitions of major co-morbidities, such as cardiac failure and COPD in published studies, markedly hinder the evaluation of the influence of these conditions on outcomes such as long-term survival after AAA repair.…”
Section: Discussionmentioning
confidence: 99%
“…16 Additionally, another study suggested that for open AAA repair patients, there was no significant association between arrival heart rate and major adverse cardiac events or 30-day mortality, irrespective of cardiac risk or beta-blocker status. 17 These data call into question whether preoperative cardiology consultation can even modify the factors that have recently been shown to increase perioperative adverse cardiac events and mortality, and that interventions implemented due to cardiology consultation may not benefit patients in this cohort.…”
Section: Discussionmentioning
confidence: 99%